Employee turnover: The hotel industry perspective - Noela Michael; Anestis Fotiadis (Journal of Tourism, Heritage & Services Marketing, 2022)
Purpose: This study analyzes employee turnover in the under-researched context of the Gulf Cooperation Council. Methods: This study uses a qualitative approach to examine the reasons for turnover and strategies adopted within the hotel sector to reduce this turnover. Results: The findings reveal that turnover reasons are organization- and employee-specific. Strategies to reduce turnover include promoting a good work environment, providing transfer opportunities, talent and development planning, and implementing exit strategies to find out employees' reasons for leaving. These findings will benefit the hotel industry's human resource planning, as most employees are expatriates, and will reduce costs in terms of new recruitment. Implications: From a context based perspective cultural differences between employees' nationalities are a reason for turnover linked to differences in salary and benefits. "Social" and "economic" value are key elements for human resource professionals to consider when developing employee benefits.
Keywords: E24; L83; J63; 330; Employee Turnover; Hospitality Industry; Human Resource Management